A national wake up call: Low sex ratio in Punjab - Walia, Ajinder; Verma, Amit (2004)
The lack of `affordability' of a girl child, coupled with high living costs are some of the reasons of lower sex ratio in states like Punjab, Haryana and Uttar Pradesh. To avoid any socio-psychological repercussions the need of the hour is to immediately implement various socio-economic, legal and welfare measures as remedies. - Reproduced.
Keywords: Sex distribution - India - Punjab; Sex distribution